A review of the economic geology of tungsten - Bowles, Michael (Rhodes University, Faculty of Science, Department of Geology, 1979)
A description of the geochemistry of tungsten is given. The geochemical properties of tungsten have a strong influence on its mineralogy, distribution and abundance in crustal rocks and rock-forming minerals , and its migration/deposition within the ore-forming and supergene environments. The behaviour of tungsten during migration, from source to site of deposition, within the crust is discussed in some detail and environments considered favourable to the concentration of tungsten ore minerals are suggested. All major types of tungsten ore deposit are described with emphasis placed on those of greater economic importance. Characteristic features of each type of deposit are particularly emphasized in order to provide clear guidelines to exploration. Hydrothermal, pyrometasomatic and stratabound tungsten deposits present themselves, economically, as the most important exploration targets. The recently developed concept of syngenetic stratabound tungsten mineralisation is outlined. Exploration for deposits of this type should be aimed predominantly, but not exclusively, at volcano-sedimentary sequences of Lower Palaeozoic age, particularly within regions known to contain occurrences of Sb and Hg. Tungsten deposits commonly contain concentrations of one or more of the following metals: Sn, Sb, Bi, Mo, Au and Ag. The presence and possible extractive value of these metals, together with commonly associated metal impurities such as As, must always be taken into account in a feasibility study,Adobe Acrobat 9.53 Paper Capture Plug-in
Keywords: Tungsten; Geology, Economic